2017
DOI: 10.5812/jjnpp.63764
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Osthole Isolated from Prangos ferulacea: Acute and Subchronic Toxicities and Modulation of Cytochrome P450

Abstract: Background: Osthole (7-methoxy-8-(3-methyl-2-butenyl)-2H-1-benzopyran-2-one), a natural coumarin derivative, has exhibited various pharmacological properties. In addition, the possibility of its development as a promising lead compound for drug discovery has been proposed. However, there is little toxicological information regarding safety of repeated exposure to this coumarin. Objective: The present study evaluated the potential toxicity of osthole after acute and subchronic administration in rodents. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Investigations of the safety of osthol (5) have found that it is moderately toxic substance when administered i. p. in rodents. The no-observed adverse-effect level of osthol (5) for both male and female rats is considered to be less than 5 mg/kg [43]. These findings suggest that osthol (5) might prove to be useful as a therapeutic agent in carcinoma treatment mainly in phenotypic-resistant cell lines due to defect in p53 function.…”
Section: Cytotoxic Activitymentioning
confidence: 89%
“…Investigations of the safety of osthol (5) have found that it is moderately toxic substance when administered i. p. in rodents. The no-observed adverse-effect level of osthol (5) for both male and female rats is considered to be less than 5 mg/kg [43]. These findings suggest that osthol (5) might prove to be useful as a therapeutic agent in carcinoma treatment mainly in phenotypic-resistant cell lines due to defect in p53 function.…”
Section: Cytotoxic Activitymentioning
confidence: 89%
“…In a subchronic study, osthole was administered to Wistar rats in doses of 5–50 mg/kg bw for 45 days, by oral route. The results showed pulmonary hemorrhage and mild inflammatory processes in kidneys and liver of the animals treated with higher doses of osthole ( Shokoohinia et al, 2017 ).…”
Section: Safety Profile Of Natural Coumarinsmentioning
confidence: 97%
“…Reviewing current literature can help to collect information regarding the bio-efficacy and safety of the administration of significant phytochemicals in the prevention and management of different malignancies and their relevant complications. Since osthol safety has been investigated, the no-observed adverse-effect level (NOAEL) of osthol for both male and female rats is considered to be less than 5 mg/kg [ 93 ]. We suggest to perform randomized, controlled, trials with adequate sample size in order to validate the safety and efficacy of osthol in managing patients with malignancies.…”
Section: Toxicity Of Ostholmentioning
confidence: 99%